What do the colours of the MET Gala reveal about Western situation? A semiotic inquiry - Losardo, Luca (AREA - Agenda de Reflexión en Arquitectura, Diseño y Urbanismo, 2025)
How can we understand which are the values circulating in a semiosphere —a topological space where meaning circulate linked to a specific culture— by looking at the colours? Our hypothesis is that, considering Oberascher’s cycle of colour phases, and confronting it with the colours trends proposed on runways, the Met Gala, and Pantone “Colour of the Year”, it is possible to attest the situation of our semiosphere, i.e., explosion, stability, growth or extinction of meaning attribution from a culture. If there is a change in the order of the cycle, it will mean an explosion of the semiosphere; if there is a stability, the colours are going to gradually change; if there is a growth, there is a rhythm; if there is extinction, there is a stagnation of a phase over prolonged time. Therefore, which is the condition of the Western semiosphere? Focusing on the colour presented at the Met Gala and on the Pantone “New Year Colour” selection, the answer that emerges is that the semiosphere is, at the moment, in an explosive phase: there are big swings in action, changes that are conducting to a switch of values related to the thirties, such as technological advancement and political recession that could lead to the extinction of the semiosphere.